2005
DOI: 10.1073/pnas.0500881102
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intercellular coupling leads to paradoxical propagation across the Purkinje-ventricular junction and aberrant myocardial activation

Abstract: Ventricular tachycardia is a common heart rhythm disorder and a frequent cause of sudden cardiac death. Aberrant cell-cell coupling through gap junction channels, a process termed gap junction remodeling, is observed in many of the major forms of human heart disease and is associated with increased arrhythmic risk in both humans and in animal models. Genetically engineered mice with cardiac-restricted knockout of Connexin43, the major cardiac gap junctional protein, uniformly develop sudden cardiac death, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 26 publications
2
61
0
2
Order By: Relevance
“…to reveal its transmural course (Ono et al, 2009). Furthermore, while the endocardial network appears dense, the number of functional PMJs is far less (Morley et al, 2005). The one-dimensional cubic Hermite finite elements are only electrically connected to the myocardium at end points through gap junctions.…”
Section: Modeling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…to reveal its transmural course (Ono et al, 2009). Furthermore, while the endocardial network appears dense, the number of functional PMJs is far less (Morley et al, 2005). The one-dimensional cubic Hermite finite elements are only electrically connected to the myocardium at end points through gap junctions.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…Currently, the number of functional PMJs is not well characterized. Although the density of the PS on the endocardium appears high, the number of penetrating segments is unknown, as is the number of PMJs that successfully transmit pulses (Morley et al, 2005). There are significant species differences in the degree of transmural penetration of terminal PS fibres.…”
Section: Description Of the Purkinje Systemmentioning
confidence: 99%
“…To overcome the mismatch, there must be a reduced sink via uncoupling or an increased source via DAD synchronization between adjacent cells. Both mechanisms have been suggested to appear under conditions of gap-junctional remodeling (Morley et al, 2005) or adrenergic stimulation (Myles et al, 2012), respectively. Following this argumentation, enhanced coupling should increase the sink and may reduce the risk of arrhythmia.…”
Section: Calcium-induced Depolarizationsmentioning
confidence: 99%
“…However, remarkable differences in action potential (AP) properties between the PF and ventricular cells [1,2] may lead to abnormalities in excitation conduction through the Purkinje-ventricular junction (PVJ) and arrhythmogenic behaviour [3][4][5]. Primarily, as action potentials (APs) from PF cells are typically longer than ventricular APs, it has been suggested that dispersion of the action potential duration (APD) at the PVJ can result in unidirectional conduction block [3], triggered activity [4] and reentry [5] under both physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, remarkable differences in action potential (AP) properties between the PF and ventricular cells [1,2] may lead to abnormalities in excitation conduction through the Purkinje-ventricular junction (PVJ) and arrhythmogenic behaviour [3][4][5]. Primarily, as action potentials (APs) from PF cells are typically longer than ventricular APs, it has been suggested that dispersion of the action potential duration (APD) at the PVJ can result in unidirectional conduction block [3], triggered activity [4] and reentry [5] under both physiological and pathological conditions.Computer simulations have been used previously in order to reconstruct APs in a single PF cell [6] and AP conduction in the whole fibre [7], as well as characterize electrotonic modulation of the APD dispersion at the PVJ [8]. However, the DiFrancesco-Noble model for a single rabbit PF cell [6] used in the latter simulations has been based on limited experimental data, whereas APs in ventricular cells were simulated using the Luo-Rudy model for a guinea-pig ventricular myocyte [9].…”
mentioning
confidence: 99%